Meningkatkan Kualitas Ibadah melalui Laboratorium Pendidikan Agama Islam untuk Siswa Sekolah Dasar - Khairul Saleh; Kemal Hidayatullah; Ravana Gustira (Jurnal Muara Pendidikan, 2026)
This study was motivated by the low quality of students' prayer practices, particularly in terms of prayer recitations and movements. The purpose of this research was to improve the quality of students' prayer performance through the utilization of the Islamic Education (PAI) Laboratory. The study employed a Classroom Action Research (CAR) design using a descriptive qualitative approach. The findings indicated that the implementation of learning activities through the PAI Laboratory effectively enhanced the quality of students' prayer practices. The research was conducted in two cycles. The first cycle consisted of two meetings, focusing on prayer recitations in the first meeting and prayer movements in the second. Assessment of students' prayer quality was then carried out during the second cycle. The results showed a significant improvement in students' prayer recitation skills, increasing from 33.3% in the preliminary stage to 75% in the second cycle, representing an improvement of 41.7%. Similarly, the quality of prayer movements improved from 50% in the pre-cycle stage to 92% in the second cycle, reflecting an increase of 42%. These findings suggest that the use of the PAI Laboratory as a practical learning medium can effectively improve students' prayer quality. Therefore, the wider application of hands-on learning methods through the PAI Laboratory is recommended in Islamic Religious Education instruction.